2003
DOI: 10.1590/s1516-35982003000400027
|View full text |Cite
|
Sign up to set email alerts
|

Substituição do farelo de soja pela farinha de glúten de milho na alimentação de cabras leiteiras

Abstract: RESUMO -Realizou-se um experimento com cabras Saanen, primíparas, pesando em média, 50 kg, alojadas em baias individuais de 3 m 2 , objetivando avaliar a substituição da proteína do farelo de soja (FS) pela proteína da farinha de glúten de milho (FGM), na produção e composição do leite, consumo voluntário e níveis de uréia plasmática. O delineamento experimental foi o triplo quadrado latino 4x4, com quatro períodos de 21 dias, sendo 14 dias de adaptação à dieta e sete dias para colheita das amostras. As cabras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
0
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
(20 reference statements)
2
0
0
3
Order By: Relevance
“…The average percentage value of 0.0435 for lactose in the milk of animals in the present study is similar to 0.043, recommended by current Brazilian legislation for goat milk (Brasil, 2000) and equal to 0.0435 found by Macedo et al (2003), who found no difference in lactose and protein levels when substituting up to 0.5 soybean meal by corn gluten in the diet of lactating goats, unlike animals fed a diet containing WC+U, which showed the percentage of 0.0429 for lactose in milk lower than the other treatments (P<0.05); the lower NFC consumption by these animals may have contributed to reduced production of propionate and consequently its availability in the mammary gland for use in the synthesis of lactose (Goestich et al, 2001). Like protein, the lactose content of milk can hardly be changed (Carvalho, 2000).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The average percentage value of 0.0435 for lactose in the milk of animals in the present study is similar to 0.043, recommended by current Brazilian legislation for goat milk (Brasil, 2000) and equal to 0.0435 found by Macedo et al (2003), who found no difference in lactose and protein levels when substituting up to 0.5 soybean meal by corn gluten in the diet of lactating goats, unlike animals fed a diet containing WC+U, which showed the percentage of 0.0429 for lactose in milk lower than the other treatments (P<0.05); the lower NFC consumption by these animals may have contributed to reduced production of propionate and consequently its availability in the mammary gland for use in the synthesis of lactose (Goestich et al, 2001). Like protein, the lactose content of milk can hardly be changed (Carvalho, 2000).…”
Section: Resultssupporting
confidence: 88%
“…The percentage of protein in milk did not differ among diets, with average percentage of 0.0341, above the 0.0299 found by Macedo et al (2003), but similar to the 0.0369 observed by Araújo et al (2010). It was expected that the different sources of protein would promote changes in the protein content, which was not observed in this study, since soybean meal, which is a food rich in rumen-degradable protein (RDP), was replaced by three sources of protein (cottonseed meal, cottonseed cake and whole cottonseed), with higher levels of rumen-undegradable protein (RUP).…”
Section: Resultssupporting
confidence: 85%
“…Mouro (2001), ao utilizar a farinha de varredura em substituição ao milho na mistura concentrada e volumoso de feno de alfafa, na proporção concentrado:volumoso de 60:40, na alimentação de cabras em lactação, não constatou diferença na produção e composição do leite. Macedo et al (2003), ao substituírem o farelo de soja pela farinha de glúten de milho na alimentação de cabras leiteiras, observaram decréscimos lineares na produção de gordura (kg/dia), no teor de gordura (%) e sólidos totais (kg/dia). No entanto, esses autores não constataram efeitos sobre os teores de proteína bruta e nos teores de sólidos totais.…”
Section: Introductionunclassified
“…Entretanto, pesquisa realizada por Freitas et al (2006), avaliando o efeito da substituição parcial do milho e do farelo de soja em rações por níveis crescentes de farelo de glúten de milho 21 (Refinazil ® ) de 0, 5, 10 e 15% sobre o desempenho produtivo de frangos de corte, concluíram que este ingrediente pode ser incluído em até 15% sem prejuízo no desempenho desses animais. Macedo et al (2003), avaliando a substituição da proteína do farelo de soja pela proteína da farinha de glúten de milho nos níveis de 0, 10, 30 e 50% (base na proteína bruta) na produção e composição do leite, consumo voluntário e níveis de uréia plasmática de cabras leiteiras, observaram que não houve efeito sobre o consumo de matéria seca, porém houve decréscimos lineares na produção de leite, teor de gordura e teor de sólidos totais. Os teores de proteína bruta, lactose e sólidos totais não sofreram efeito dos níveis de substituição e os níveis de uréia plasmática foram inferiores para os menores níveis de substituição.…”
Section: Farelo De Glúten De Milho 21unclassified